Asuhan Keperawatan Jiwa Pada Pasien dengan Resiko Perilaku Kekerasan di Wisma Nuri RSJ. Prof. HB. Sa’anin Padang Tahun 2026 - afiva nabila putri rinaldi; Dwi Happy Anggia Sari; Vivi Yuderna; Ramaita . (CV. ITTC INDONESIA, 2026)
Mental disorders are conditions characterized by disturbances in cognitive function, emotional regulation, and behavior, which affect an individual’s ability to perform daily activities (American Psychiatric Association, 2022). The World Health Organization (WHO) defines mental disorders as clinically significant disturbances accompanied by psychological distress and impaired functioning in important areas of life (WHO, 2025). Globally, approximately 970 million people experienced mental disorders in 2023, increasing to more than 1.1 billion in 2024. In Indonesia, the prevalence of mental disorders in West Sumatra Province is 1.3% (Indonesia Health Survey, 2023). One of the common problems found in severe mental disorders such as schizophrenia is the risk of violent behavior, which is a maladaptive response due to the inability to control aggressive impulses that may harm oneself, others, and the environment. Data from RSJ Prof. Dr. HB. Saanin Padang indicate that the risk of violent behavior is the second most common nursing problem after hallucinations. This study aims to describe psychiatric nursing care for patients with a risk of violent behavior in Wisma Nuri at RSJ Prof. Dr. HB. Saanin Padang in 2026. The method used is a case study with the implementation of the Nursing Intervention Strategy (SP), including physical exercises, medication adherence, verbal emotional control, and spiritual approaches over five days. The results showed an improvement in the patient’s ability to control emotions and behavior. It can be concluded that comprehensive psychiatric nursing care is effective in reducing the risk of violent behavior.